Effects of Maternal Work Incentives on Adolescent Social Behaviors - Dhaval M. Dave; Hope Corman; Ariel Kalil; Ofira Schwartz-Soicher; Nancy E. Reichman (Institute of Labor Economics (IZA), 2019)
This study investigates the effects of welfare reform in the U.S. in the 1990s, which dramatically limited cash assistance for low-income families, on the next generation as they transition to adulthood. We estimate effects by gender and focus on behaviors that are important for socioeconomic and health trajectories and represent early observable consequences of the reforms for the next generation. Using two nationally-representative datasets, we exploit differences in welfare reform implementation across states and over time in a difference-in-difference-in-differences framework to identify plausibly causal effects of welfare reform on a range of prosocial and antisocial behaviors (volunteering, participating in clubs/teams/activities, skipping school, getting into fights, damaging property, stealing, hurting others, smoking, using alcohol, using marijuana, using other illicit drugs). We explore maternal employment, supervision, and child's employment when not in school as potential mediators. We find that: (1) Welfare reform had no favorable effects on any of the youth behaviors examined. (2) Welfare reform led to a decrease in volunteering among girls. (3) Welfare reform led to increases in skipping school, damaging property, and getting into fights among boys. (4) Welfare reform led to increases in smoking and drug use among both boys and girls, with generally larger effects for boys (e.g., approximately 6% for boys compared to 4% for girls for any substance use). (5) The mediators we are able to consider explain little of the observed effects of welfare reform. Overall, the results from this study suggest that the intergenerational effects of welfare reform on adolescent behaviors were unfavorable, particularly for boys, and do not support longstanding arguments that incentivizing maternal employment by limiting cash assistance leads to responsible behavior in the next generation. As such, the social gains of welfare reform for women found in previous studies may have come at a cost to the next generation, particularly to boys who have been falling behind girls in terms of high school completion for decades.
Keywords: H53; I12; I31; I38; 330; welfare reform; maternal work; substance use; violence; school; intergenerational; adolescents; risky behaviors